Human nature and state of education in Rousseau: Society (Pulso. Revista de educación, 2002)
According to Rousseau, society is a being that is “condemned” to fluctuate throughout historical Evolution, and within it, the concepts of good and the principles of justice are applied to human nature.Education, which is a crucial concept in Rousseau's work, enables us to examine the states of humanity, particularly those related to children and their “upbringing”.  The goal is to search for and/or rediscover the blissful instinct that we all abandon as we begin to live within a community.